Mirrored, imagined and executed movements differentially activate sensorimotor cortex in amputees with and without phantom limb pain - Diers, Martin; Christmann, Christoph; Köppe, Caroline; Ruf, Matthias; Flor, Herta (Pain, 2010)
Extended viewing of movements of the intact hand in a mirror as well as motor imagery has been shown to decrease pain in phantom pain patients. We used functional magnetic resonance imaging to assess the neural correlates of mirrored, imagined and executed hand movements in 14 upper extremity amputees - 7 with phantom limb pain (PLP) and 7 without phantom limb pain (non-PLP) and 9 healthy controls (HC). Executed movement activated the contralateral sensorimotor area in all three groups but ipsilateral cortex was only activated in the non-PLP and HC group. Mirrored movements activated the sensorimotor cortex contralateral to the hand seen in the mirror in the non-PLP and the HC but not in the PLP. Imagined movement activated the supplementary motor area in all groups and the contralateral primary sensorimotor cortex in the non-PLP and HC but not in the PLP. Mirror- and movement-related activation in the bilateral sensorimotor cortex in the mirror movement condition and activation in the sensorimotor cortex ipsilateral to the moved hand in the executed movement condition were significantly negatively correlated with the magnitude of phantom limb pain in the amputee group. Further research must identify the causal mechanisms related to mirror treatment, imagined movements or movements of the other hand and associated changes in pain perception.